2021
DOI: 10.1124/jpet.121.000840
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Two Structurally Related Dipeptides that Enhance Catalytic Efficiency of Neurolysin

Abstract: Neurolysin (Nln) is a recently recognized endogenous mechanism functioning to preserve the brain from ischemic injury. To further understand the pathophysiological function of this peptidase in stroke and other neurological disorders, the present study was designed to identify small molecule activators of Nln.Using a computational approach, the structure of Nln was explored, followed by docking and in silico screening of ~140,000 molecules from the National Cancer Institute Developmental Therapeutics Program d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…with synthetic substrates may be misleading in identification of enzyme modulators (Jayaraman et al, 2021), in this set of experiments the concentration-dependent effect of DIZE on hydrolysis of Ang II by ACE2 was studied using mass spectrometry and no substantial differences were documented (Fig. 4).…”
Section: Effect Of Dize On Ace2-mediated Formation Of Ang-(1-7) From ...mentioning
confidence: 94%
See 2 more Smart Citations
“…with synthetic substrates may be misleading in identification of enzyme modulators (Jayaraman et al, 2021), in this set of experiments the concentration-dependent effect of DIZE on hydrolysis of Ang II by ACE2 was studied using mass spectrometry and no substantial differences were documented (Fig. 4).…”
Section: Effect Of Dize On Ace2-mediated Formation Of Ang-(1-7) From ...mentioning
confidence: 94%
“…For ACE2 we used fluorogenic substrate Mca-Ala-Pro-Lys (Dnp) (Kulemina and Ostrov, 2011), for ACE and NEP, Mca-Arg-Pro-Pro-Gly-Phe-Ser-Ala-Phe-Lys(Dnp)-OH (Johnson and Ahn, 2000;Wösten-van Asperen et al, 2008) and for Nln and TOP, Mca-Pro-Leu-Gly-Pro-D-Lys(Dnp)-OH (Jayaraman et al, 2021). As detailed in results section, the first set of experiments were carried out in 75 mM Tris-HCl 0.1 M NaCl, 0.5 µM ZnSO 4 and 0.01% Triton-X (pH 7.4) which is the same assay buffer used in the original study reporting discovery of DIZE as an ACE2 activator (Kulemina and Ostrov, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed SAR studies identified analogues 25–27 with increased activities over the original hit (AC 50 of 6.5 μM, 4.2 μM and 7.0 μM for compounds 25 , 26 and 27 respectively). 207–210 In vitro metabolic stability studies reported that each of the three analogues had significantly increased half-lives in mouse plasma compared to the original hit, which reported a half-life of 34.19 minutes, in comparison to compounds 25 and 26 , which presented the best half-lives of >1000 minutes. 205 The permeabilities of each of the compounds were obtained within the MDR1-MDCA cell line, in which 26 and 27 presented the best permeability.…”
Section: Neurolysinmentioning
confidence: 99%
“…The development of small-molecule enzyme activator compounds is rapidly becoming a viable therapeutic discovery strategy for many diseases. , In our efforts to identify Nln activator compounds for stroke, we previously disclosed a peptido­mimetic scaffold represented by Nln-10c and Nln-11a , optimized from a dipeptide hit ( HY ) obtained from a high-throughput screen (Figure ). Both compounds possessed “drug-like” pharmaco­kinetic parameters, including brain penetration. Additionally, compound Nln-11a was determined to preferentially accumulate in the ischemic hemisphere of the IS middle cerebral artery occlusion (MCAO) mouse model .…”
mentioning
confidence: 99%